A CONTAÇÃO DE FÁBULAS DE ESOPO ADAPTADAS COM RECURSO DA COMUNICAÇÃO ALTERNATIVA E AMPLIADA PARA CRIANÇAS COM TRANSTORNO DO ESPECTRO AUTISTA - Scariott, Gabriela Christine (2024)
The ability to understand stories plays a crucial role in child development and can pose significant challenges for children diagnosed with Autism Spectrum Disorder (ASD) due to difficulties in communication and social interaction. This study aims to investigate the comprehension of adapted Aesop's fables using Augmentative and Alternative Communication (AAC) in two groups of children with ASD who are participants of the Guarapuavan Blue World Association (AGMA). To achieve this goal, five Aesop's fables, namely “The Playful Shepherd”, “The Horse and the Donkey”, “The Cicada and the Ants”, “The Donkey Pretending to Be a Lion” and “The Fox and the Goat”, were selected and adapted into a more accessible format by integrating AAC cards. These cards were developed based on pictograms from the ARASAAC system, available in the website's database, by Researcher Gabriela (PG). The result was the production of ten fable books, with five adapted with AAC cards and five containing only the main image related to the text. After completing the development of the fables, including defining the visual identity, color selection, outlines, painting, visual enhancement of characters and scenes, and choosing the font for the text and pictograms, two distinct versions of the five selected fables were created. The instruments were pre-tested in a pilot study and then applied to two groups of participants. The field analysis included: a) Application Group (AG), consisting of three boys with ASD, investigating the strengths and limitations of the fables adapted with AAC; b) Control Group (CG), establishing a comparison baseline for the data obtained in the AG. The research adopted a qualitative approach, formulating five questionnaires, one for each fable, administered in six individual sessions, one per week.The results of this research highlight the promising effectiveness of AAC in enhancing the understanding of stories by children with ASD in the early stages of literacy. Similarly, data revealed during the field research support the relevance of AAC as a valuable tool for promoting educational inclusion, overcoming communicative challenges, and contributing to the active participation of these children in the school context.